Provider Delivery of Emergency Preparedness Education in Home Based Primary Care - Wyte-Lake, Tamar (Disaster Med Public Health Prep, 2018)
INTRODUCTION: Home health agencies have been tasked to improve their patients’ disaster preparedness. Few studies have evaluated the robustness of tools to support preparedness in home health. Through evaluation of the Home-Based Primary Care (HBPC) Patient Assessment Tool (“Tool”), we conducted a survey to identify strengths and challenges in supporting the preparedness of patients served by home health programs such as the Veterans Health Administration’s HBPC program. METHODS: Practitioners from 10 HBPC programs fielded the Tool with all patients during a three-week period. Logistic regression and bivariate analyses were used to identify patient characteristics associated with the delivery of preparedness education. RESULTS: 754 Patient Assessment Tools were returned. The educational item most likely to be covered was how to activate 911 services (87%). The item least likely to be discussed was information on emergency shelter registration and emergency specialty transportation (44%). When compared to the “low” risk group, HBPC patients in the “high/medium” risk group were more likely to receive preparedness education materials for six of the nine educational preparedness items (p’s<0.05). DISCUSSION: Practitioners are relaying preparedness education to their most vulnerable patients, suggesting that home health agencies can provide disaster preparedness in the home. Nonetheless, there is room for improvement.